Synthesis and structure of two palladium(II) complexes bearing acetonitrile and N-heterocyclic carbene derived from imidazole - Mai, Truong Thi Cam; Chi, Nguyen Thi Thanh (Vietnam Journal of Science and Technology, 2019)
The reaction of [PdCl2(CH3CN)2] (1) with either 1,3-bis(2,4,6-trimethylphenyl)imidazolium chloride (IMes·HCl) or 1,3-bis(2,6-diisoproylphenyl)imidazolium chloride (IPr·HCl) in the present of Ag2O afforded two mixed monocarbene-CH3CN complexes, namely trans-[PdCl2(CH3CN)(IMes] (2) and trans-[PdCl2(CH3CN)(IPr)] (3), with the high yield (85-90%). The structure of 2 and 3 were elucidated by ESI mass, IR, 1H NMR and 13C NMR spectra. For 2, single-crystal X-ray diffraction study was also carried out. The results show that the CH3CN in 2 and 3 coordinates with Pd(II) via the N atom, the deprotonated imidazolium salts are bound up with Pd(II) via the C atom (NCHN) and occupy trans-position in comparison with the CH3CN.